Functional Management of Marketing Internet Activities of Enterprises - Boychuk, Inna (Bulletin of Yerevan University G: Economics, 2016)
The article analyzes the peculiarities of functional management of marketing activity of the enterprises on the Internet. The basic advantages of the network are taking into account the assessment of changes, taking place in the business processes on the Internet. Internet marketing is considered as a process to meet the needs of consumers with network capabilities. In terms of the basic functions of marketing different aspects of marketing tools online are considered. The implementation of these functional areas of marketing activity allows more effective development and implementation of the marketing strategy.
Keywords: Information technology, business, Internet, internet marketing, marketing activities, function’s complex of marketing, strategies